Relevance of biomarkers indicating gut damage and microbial translocation in people living with HIV - Ouyang, Jing; Yan, Jiangyu; Zhou, Xin; Isnard, Stéphane; Harypursat, Vijay; Cui, Hongjuan; Routy, Jean-Pierre; Chen, Yaokai (Frontiers in Immunology, 2023)
The intestinal barrier has the daunting task to allow nutrient absorption while limiting the entry of microbial products into the systemic circulation. HIV infection disrupts the intestinal barrier, and increases intestinal permeability leading to microbial product translocation. Convergent evidence has shown that gut damage and an enhanced level of microbial translocation contribute to the enhanced immune activation, risk of non-AIDS comorbidity, and mortality in people living with HIV (PLWH). Gut biopsy is invasive and not suitable in large population even though it is the gold standard for intestinal barrier study, and thus, validated biomarkers to measure the degree of intestinal barrier damage and microbial translocation are needed in PLWH. Blood biomarkers should represent an objective indication of specific medical conditions and/or its severity, and be measured accurately and reproducibly by easily available and standardized blood tests. Several plasma biomarkers of intestinal damage like intestinal fatty acid-binding protein (I-FABP), zonulin, regenerating islet-derived protein-3α (REG3α), and biomarkers of microbial translocation, such as lipopolysaccharide (LPS) and (1,3)-β-D-Glucan (BDG), have been used as markers of risk of developing non-AIDS comorbidities in cross sectional analyses and clinical trials, including those aiming at repairing gut damage. In this review, we critically discuss the value of different biomarkers for the estimation of gut permeability levels, paving the way towards developing validated diagnostic and therapeutic strategies to repair the gut epithelium damage and improve disease outcomes in PLWH.